Development of an experimental setup for micro flow measurement using the front tracking method. (December 2021) - Batista, Elsa; Sousa, João A.; Álvares, Miguel; Afonso, Joana; Martins, Rui F.
Abstract: This work has the main objective to develop a method for microflow measurement using the front tracking principle under the project MeDD II – Metrology for Drug Delivery. The experimental setup uses a high-resolution camera and an image processing software to track the distance travelled by the meniscus of a liquid in a capillary tube and calculate the flow rate. Experimental tests using a flow generator were carried out for different flow rates using two different cameras. To validate the developed front tracking method, an internal comparison was made with the gravimetric method in LVC. The results obtained by this comparison were consistent. This developed method can be used to calibrate flow devices down to 1 μL/h with an uncertainty value of 7% ( k = 2).